Evaluation of thermal stability and damping behavior of electrical insulator waste reinforced thermoset polymer composite. (May 2019) - Sabarinathan, P; Annamalai, VE; Rajkumar, K
This paper deals with the influence of inorganic electrical insulator waste filler on the properties of glass fiber reinforced epoxy composite. The electrical insulator waste fillers were uniformly mixed in the resin through ultrasonication technique. Composites were made up with different percentages of filler (0, 5, 10, 20 wt%) and 20 wt% glass fiber using the hand lay-up method. Physical, mechanical, water absorption, thermal, and dynamic mechanical properties were studied. The experimental results indicate an increase in water absorption and density of composites with increased electrical insulator waste filler in the polymer matrix. Furthermore, the filler addition reduces the tensile strength and increases the flexural strength to 402 MPa at 20% addition. The thermogravimetric analysis reveals that the incorporation of electrical insulator waste filler increases the thermal stability considerably. Dynamic property reveals the damping property of the materials, in which the incorporation of 20% filler leads to higher storage modulus. Particle dispersion and failure mode were analyzed using scanning electron microscope. This work highlights the possibility for reprocessing electrical insulator waste as low-cost reinforcement in polymer composites.